Surface nanostructures on Nb-doped SrTiO3 irradiated with swift heavy ions at grazing incidence. (4th June 2022) - Ishikawa, N; Fujimura, Y; Kondo, K; Szabo, G L; Wilhelm, R A; Ogawa, H; Taguchi, T
Abstract: A single crystal of SrTiO3 doped with 0.5 wt% niobium (Nb-STO) was irradiated with 200 MeV Au 32+ ions at grazing incidence to characterize the irradiation-induced hillock chains. Exactly the same hillock chains are observed by using atomic force microscopy (AFM) and scanning electron microscopy (SEM) to study the relation between irradiation-induced change of surface topography and corresponding material property changes. As expected, multiple hillocks as high as 5–6 nm are imaged by AFM observation in tapping mode. It is also found that the regions in between the adjacent hillocks are not depressed, and in many cases they are slightly elevated. Line-like contrasts along the ion paths are found in both AFM phase images and SEM images, indicating the formation of continuous ion tracks in addition to multiple hillocks. Validity of preexisting models for explaining the hillock chain formation is discussed based on the present results. In order to obtain new insights related to the ion track formation, cross-sectional transmission electron microscopy (TEM) observation was performed. The ion tracks in the near-surface region are found to be relatively large, whereas buried ion tracks in the deeper region are relatively small. The results suggest that recrystallization plays an important role in the formation of small ion tracks in the deep region, whereas formation of large ion tracks in the near-surface region is likely due to the absence of recrystallization. TEM images also show shape deformation of ion tracks in the near-surface region, suggesting that material transport towards the surface is the reason for the absence of recrystallization.